Is the value of bioprospecting contracts too low? - Anil Markandya; Paulo A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2010)
In order to regulate the proliferated bioprospecting and protect the biological diversity in the source countries, the Convention on Biological Diversity (CBD) established a legal framework for the reciprocal transfer of biological materials between the interested parties in bioprospecting activities, subject to the Prior Informed Content (PIC) principles and a set of mutually agreed items on equitable sharing of benefits (CBD 1992, Bhat 1999; Ten Kate and Laird 1999; Dedeurwaerdere 2005). Although interesting and valuable to the cause of conservation, there is a feeling that the 'price' being paid under these arrangements is too low. Somehow ecologists argue that, surely, these materials have a greater value than the few million dollars being paid to national conservation organizations for the protection of the areas where the material are located. In this paper we seek to understand better how a biodiversity resource' use value in production is determined, and how the real value is obscured by the fact that the resource is largely open access. We attempt to analyse how special arrangements, set op top of a basic framework in which the resource open access is limited in what it can achieve and in the 'price' that will emerge from any transaction between the buyers of the rights and the sellers of the rights.
Keywords: D21; D23; D61; L14; Q57; 330; Access and Benefit Sharing; Convention for Biological Diversity; Bioprospecting Contract; Genetic Resource; Open Access and Welfare Analysis